2023
DOI: 10.3389/fcimb.2023.1145215
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus infection and common sexually transmitted infections, and the clinical significance of different Mycoplasma subtypes

Abstract: IntroductionHuman papillomavirus (HPV) infection, especially persistent high-risk HPV, is associated with cervical cancer. Female reproductive tract microecological disorders and lower genital tract infections have been increasingly correlated with HPV infection and cervical lesions. Due to their common risk factors and transmission routes, coinfection with other sexually transmitted infections (STIs) has become a concern. Additionally, the clinical significance of Mycoplasma subtypes appear to vary. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…As for M. genitalium infection, there is limited research on its association with HPV infection and cervical lesions. A study by A et al found no association between M. genitalium infection and HPV infection or cervical lesions [ 9 ], which is consistent with our findings. Currently, most studies are cross-sectional or retrospective.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As for M. genitalium infection, there is limited research on its association with HPV infection and cervical lesions. A study by A et al found no association between M. genitalium infection and HPV infection or cervical lesions [ 9 ], which is consistent with our findings. Currently, most studies are cross-sectional or retrospective.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have indicated an association between C. trachomatis infection and HPV infection as well as cervical lesions [ 8 , 23 ]. However, other studies have suggested that C. trachomatis infection does not increase the risk of HPV infection and cervical lesions [ 9 , 10 , 25 ], which aligns with our research findings. The conflicting results may stem from differences in cohorts or limitations in sample size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 271 Phenylactic acid, a phenolic acid phytochemical predominantly produced by L actobacillus , represses E6/E7 expression while promoting cervical cancer cell migration and via IKK/NF‐κB‐mediated MMP‐9 activation. 272 Additionally, coinfections in the vaginal microenvironment, such as Chlamydia trachomatis, 273 , 274 herpes simplex virus2, Ureaplasma urealyticum, 275 can increase the risk of HPV‐associated cervical lesion and cancer; some of these coinfections influence the expression HPV oncogene. 276 Researchers have found that the presence of specific anaerobic taxa, including Megasphaera , P revotella timonensis , and Gardnerella vaginalis , is associated with CIN2 persistence and slower regression, 277 suggesting that VMB composition may serve as a useful biomarker for predicting disease outcome and tailoring surveillance in the future.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%